ANALISIS PENINGKATAN KESEJAHTERAAN RAKYAT DAN PENGURANGAN KEMISKINAN DI DISTRIK DILI, TIMOR LESTE TAHUN 2004-2009 - , Paulo Alves, S.E., Drs. Ahmad Jamli, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to: 1) analyzing how big the influence of GDP, the quality of Human Resources, Public Expenditure on the level of poverty in the District dili year 2004-2009. 2) Measure and analyze gaps and between economic growth between sub-districts of Dili Year 2004-2009. This research uses descriptive analytical tool, to determine the economic growth and not balance between sub- District se dili District and quantitative, to analyze the Improvement of People's Welfare and Poverty Reduction dili In the District, to measure not banlace development among the sub-district in Dili District using the regional index (regional inequality) index of inequality Williamson, curves and regression kuznet polling data. The results showed that: 1. there is a negative influence between GDP per capita with the level of poverty